Standardised regression coefficient as an effect size index in summarising findings in epidemiological studies (Epidemiology, Biostatistics, and Public Health, 2022)
Background: a major problem in evaluating and reviewing the published findings of studies on the association between a quantitative explanatory variable and a quantitative dependent variable is that the results are analysed and reported in many different ways. To achieve an effective review of different studies, a consistent presentation of the results is necessary. This paper aims to exemplify the main topics related to summarising and pooling research findings from multivariable models with a quantitative response variable.Methods: we outline the complexities involved in synthesising associations. We describe a method by which it is possible to transform the findings into a common effect size index which is based on standardised regression coefficients. To describe the approach we searched original research articles published before January 2012 for findings of the relationship between polychlorinated biphenyls (PCBs) and birth weight of new-borns. Studies with maternal PCB measurements and birth weight as a continuous variable were included.Results: the evaluation of 24 included articles reveled that there was variation in variable measurement methods, transformations, descriptive statistics and inference methods. Research syntheses were performed summarizing regression coefficients to estimate the effect of PCBs on birth weight. A birth weight decline related to increase in PCB level was found.Conclusions: the proposed method can be useful in quantitatively reviewing published studies when different exposure measurement methods are used or differential control of potential confounding factors is not an issue.